World Philosophy Day 2022: The Human of the Future (Based on the materials of the symposium “The Human of the Future,” November 16-18, 2022, UNESCO, Paris) - Kseniia Fedorova (Философия и космология, 2023)
The paper is devoted to reviewing the materials of “The Human of the Future” symposium, which took place at UNESCO Headquarters from 16 to 18 November on the occasion of the World Philosophy Day. In a hyper-technological world, the very concept of humanity undergoes constant evolution. In view of the scale of modern challenges, within the framework of the event, it was suggested to reflect upon the concept of “the human of the future” from the point of view of their own evolution and historical development, as well as from the viewpoint of the world upheavals causing human to overflow and surpass their own historical formation. The purpose of the article is to determine contemporary philosophical and anthropological tendencies in the development of Humanities and Social studies and to examine the status of a philosophical approach as relevant to the digital world for understanding the “human”. The theoretical basis is represented by the materials of the speeches of contemporary philosophers, anthropologists and researchers within the framework of “The Human of the Future” symposium and focused on the search for alternative anthropocentrism ways of understanding human and technology. Conclusions. The future is presented as a challenge faced with a number of serious crises in the context of information overload and unstoppable speed of data flows circulation. Studying the process of multiplying technological updates and human transformations leads to the idea of reconstructing the nature of philosophical research. Two philosophical and anthropological trends are presented: the expansion of the understanding of “human” through the introduction of technological objects and the biogeophysical dimension into its interpretation, as well as the process of ontologization of digital technologies. There is specified a range of current issues in the Social Sciences and Humanities research: communication between species, life definition, ambiguous relationship of people with technology, with increasingly blurred boundaries between technology and biology.